Analysis of Socio-Economic Impact of the Community Empowerment Program for Weaver Woman (Perempuan Penenun Ikat) in Letmaffo Village, Insana Tengah, North Central Timor District - Hilaria Diana Wati Nese Tuames; Petrus Kase; Nursalam Nursalam (Program Pascasarjana Universitas Negeri Makassar, 2020)
ABSTRACTThis research is intended to analyze and describe the Socio-Economic Impact of the Ikat Weaving Women's Group Empowerment Program in Letmaffo Village, Insana Tengah District, North Central Timor Regency. To answer this problem, it is supported by various theories that have relevance to the research phenomenon. This research is a qualitative study using the Milles and Huberman data analysis technique. The results of the study explain that the socio-economic impact on the weaving empowerment group also faces many obstacles, namely related to indicators of increasing household economy, this has not been going well because the economic income of group members has even decreased due to low productivity results and low prices woven fabrics in the market, another obstacle is the indicator of the development of the group's economic structure on this indicator, the goal is that this group of weaving ties must have a market place or place to market productivity results but this has not been achieved so that the village of Letmaffo weaving group still uses the long time in sales even productivity. The factors that support and hinder the socio-economic impact on the empowerment of the Letmaffo village weaving group are lack of capital, limited human resources, weak business networks, use of traditional production tools and limited market access.Key words: socio-economic impact, empowerment of the weaving group.